Composite electrostatic spinning membrane and preparation method thereof

Through the composite electrospinning film with a layered structure, combined with electrospinning and hot pressing treatment technology, the existing proton exchange membrane is easily degraded and insufficient proton conductivity under high temperature conditions, achieving high mechanical strength and low methanol The effect of permeability.

CN119121649APending Publication Date: 2024-12-13HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411292271.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing perfluorosulfonic acid-type proton exchange membrane is prone to degradation under high temperature conditions, and the methanol fuel permeability is high, so it is impossible to fully utilize the performance advantages of direct methanol fuel cells. The proton conductivity is insufficient, which limits the application of composite proton exchange membranes.

Method used

A composite electrospinning film with a layered structure includes an upper layer, an intermediate layer and a lower layer. The intermediate layer contains polyimide and perfluorosulfonic acid. It is prepared by electrospinning method, combined with hot pressing treatment and coating technology to form a Membrane with excellent mechanical strength and proton conductivity.

Benefits of technology

The thermal stability, mechanical strength and swelling resistance of the composite electrospinning film are improved, the permeability of methanol is reduced, the proton conductivity is improved, and the performance under high temperature conditions is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005044957150000061
    Figure BDA0005044957150000061
  • Figure BDA0005044957150000071
    Figure BDA0005044957150000071
Patent Text Reader

Abstract

The invention discloses a composite electrostatic spinning membrane and a preparation method thereof, the composite electrostatic spinning membrane is of a layered structure, the layered structure sequentially comprises an upper layer, a middle layer and a lower layer from top to bottom, the upper layer comprises perfluorosulfonic acid, the middle layer comprises polyimide and perfluorosulfonic acid, and the lower layer comprises perfluorosulfonic acid. According to the composite electrostatic spinning membrane, the problem that the conductivity of a perfluorosulfonic acid membrane is obviously reduced under the high-temperature condition is solved, the swelling resistance, the size stability, the mechanical strength and the durability of the composite electrostatic spinning membrane are improved, and the methanol permeability is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a composite electrostatic spinning membrane and a preparation method thereof. Background Art

[0002] Fuel cells have become the most competitive alternative power source in the field of internal combustion engine power due to their excellent characteristics such as high conversion rate and no pollution. In recent years, under the strong advocacy of government departments, the application of fuel cells in the field of new energy vehicles has developed rapidly. Since methanol is a fuel that is safer, easier to store and transport, and faster to refuel than hydrogen, direct methanol fuel cells are more suitable for use as portable fuel cells, which has attracted widespread attention. Proton exchange membrane is one of its core components, which is responsible for providing channels for the migration and transport of protons and blocking fuel. Therefore, its comprehensive performance is crucial for the development of high-performance direct methanol fuel cells. The currently used perfluorosulfonic acid proton exchange membrane (Nafion) has excellent electrochemical properties, acceptable mechanical strength, high proton conductivity and good oxidation stability. However, it has poor barrier effect on methanol fuel, is easy to degrade under high temperature conditions, has high fuel permeability, and has large water swelling, which cannot give full play to the performance advantages of direct methanol fuel cells. Therefore, more and more research is devoted to the research and development of fluorine-containing or non-fluorine proton exchange membranes.

[0003] Polyimide (PI) is a kind of high molecular polymer containing cyclic imide groups in the molecular chain. It has the advantages of excellent high temperature resistance, low temperature resistance, high dimensional stability, high electrical insulation, corrosion resistance, etc. There are many methods for preparing polyimide nanofiber membranes using polyimide, such as CN 102709576 A discloses a composite proton exchange membrane for high temperature fuel cells and a preparation method thereof, which is based on UV laser etching of a composite proton exchange membrane of a polyimide matrix, and is composed of a polyimide matrix film with a uniform and ordered through-hole structure, and a perfluorosulfonic acid resin membrane is prepared by impregnation. The composite proton exchange membrane prepared by this method has the characteristics of high temperature water retention, high mechanical strength, low gas permeability, and low swelling stress, but does not greatly improve the proton conductivity, which limits the practical application of the composite proton exchange membrane. Summary of the invention

[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide a composite electrospinning membrane.

[0005] Another object of the present invention is to provide a method for preparing the composite electrospinning membrane.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] A composite electrostatic spinning membrane has a layered structure, which comprises an upper layer, a middle layer and a lower layer from top to bottom. The upper layer comprises perfluorosulfonic acid, the middle layer comprises polyimide and perfluorosulfonic acid, and the lower layer comprises perfluorosulfonic acid.

[0008] In the above technical solution, the thickness of the composite electrospinning membrane is 25 to 40 μm.

[0009] In the above technical solution, the thickness of the middle layer is 15-25 μm, the thickness of the upper layer is 4-8 μm, and the thickness of the lower layer is 4-8 μm.

[0010] In the above technical solution, the ratio of polyimide to perfluorosulfonic acid in the intermediate layer is (0.1-1.5):(0.01-0.1) by mass.

[0011] In the above technical solution, the areas of the upper layer, the middle layer and the lower layer are the same.

[0012] The method for preparing the composite electrospinning membrane comprises the following steps:

[0013] Step 1, electrospinning the composite solution, drying it, and hot pressing it to obtain a spinning membrane, wherein the composite solution comprises: polyimide and perfluorosulfonic acid, and in the composite solution, the ratio of polyimide to perfluorosulfonic acid is (0.1-1.5):(0.01-0.1) by weight;

[0014] In step 1, the spinning rate of the electrospinning is 0.8-2.0 mL / h, the voltage of the electrospinning is 10-30 KV, and the distance between the spinneret and the receiving device is 15-30 cm.

[0015] In step 1, the drying temperature is 50 to 150° C., and the drying time is 10 to 20 hours.

[0016] In step 1, the hot pressing treatment is: hot pressing at 60-120° C. and 0.2-2 MPa for 5-60 min.

[0017] In step 1, the method for obtaining the composite solution is: mixing the polyimide solution and the perfluorosulfonic acid solution, stirring at 40 to 60° C. for 2 to 3 hours until the mixture is uniform, to obtain the composite solution.

[0018] In the above technical solution, the polyimide solution includes polyimide, and the polyimide in the polyimide solution is 8-14 wt %.

[0019] In the above technical solution, the perfluorosulfonic acid solution includes perfluorosulfonic acid, and the content of perfluorosulfonic acid in the perfluorosulfonic acid solution is 3-6 wt %.

[0020] In the above technical scheme, the method for preparing a polyimide solution comprises: mixing a first solution and a second solution to obtain a polyamic acid solution under a nitrogen or inert gas atmosphere, mixing the polyamic acid solution and a third solvent to obtain a third solution, mixing the third solution and an imidization agent, and stirring at room temperature for 12 to 36 hours to obtain a polyimide solution, wherein the first solution is a mixture of a diamine and a first solvent; the second solution is a mixture of a dianhydride and a second solvent, the imidization agent is a mixture of acetic anhydride and pyridine, and the ratio of diamine, dianhydride, acetic anhydride and pyridine is (0.5-4.5):(0.5-4.5):(1.2-6.5):(0.1-2.2) in terms of the amount of the substance.

[0021] In the method for preparing a polyimide solution, a first solution and a second solution are mixed, and stirred at 0 to 40° C. for 4 to 12 hours until uniform, to obtain a polyamic acid solution, wherein the first solution and the second solution are mixed by adding the second solution to the first solution in multiple portions under stirring conditions.

[0022] In the method for preparing a polyimide solution, the solid content of the third solution is 10 to 14 wt %.

[0023] In the method for preparing a polyimide solution, a method for obtaining a first solution is: diamine and a first solvent are mixed evenly to obtain the first solution; a method for obtaining a second solution is: dianhydride and a second solvent are mixed evenly to obtain the second solution, the ratio of the mass fraction of the diamine to the volume fraction of the first solvent is (0.5-2):(5-10), the ratio of the mass fraction of the dianhydride to the volume fraction of the second solvent is (0.5-2):(5-12), the unit of the mass fraction is g, and the unit of the volume fraction is mL.

[0024] In the above technical scheme, the diamine is 3,3'-dimethyl-4,4'-diaminodiphenylmethane (DMMDA), and the dianhydride is one or a mixture of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), pyromellitic anhydride (PMDA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA) and 3,3',4,4'-tetracarboxylic diphenyl ether dianhydride (OPDA).

[0025] In the method for preparing a polyimide solution, the first solvent, the second solvent and the third solvent are the same, and the first solvent, the second solvent and the third solvent are N-methylpyrrolidone (NMP).

[0026] In the above technical solution, the method for preparing the perfluorosulfonic acid solution comprises: mixing the perfluorosulfonic acid powder and the fourth solvent, reacting at 140 to 160° C. for 3 to 5 hours, and obtaining the perfluorosulfonic acid solution.

[0027] In the method for preparing a perfluorosulfonic acid solution, the fourth solvent is one or a mixture of N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, acetone and ethanol.

[0028] Step 2: coating the perfluorosulfonic acid solution on both sides of the spinning membrane, allowing it to stand and dry to obtain a composite electrospinning membrane.

[0029] In step 2, the standing time is 10 to 30 minutes.

[0030] In step 2, the drying temperature is 60-120° C., and the drying time is 5-10 hours.

[0031] In step 2, the coating method is one of cast coating, blade coating and spray coating, preferably cast coating.

[0032] Application of composite electrospun membranes in improving thermal stability, mechanical stability and / or proton conductivity of separators.

[0033] Application of composite electrospinning membrane in suppressing methanol permeability of diaphragm.

[0034] Compared with the prior art, the beneficial effects of the present invention are: the composite electrospun membrane of the present invention improves the problem of obvious decrease in conductivity of the perfluorosulfonic acid membrane under high temperature conditions, improves the anti-swelling property, dimensional stability, mechanical strength and durability of the composite electrospun membrane, and reduces the methanol permeability. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0036] Electrospinning is a process that uses high-voltage electrostatic force to drive polymer solution (or melt) to spray and form polymer fibers. The method of preparing nanofibers by electrospinning has the advantages of low cost, simple operation, and the ability to continuously prepare nanofibers with controllable morphology. The preparation of nanofiber materials by electrospinning has broad application prospects in the field of battery separators.

[0037] The raw material information involved in the following examples is as follows:

[0038] Polyimide (PI) is a type of high molecular polymer containing cyclic imide groups in its molecular chain. It has the advantages of excellent high temperature resistance, low temperature resistance, high dimensional stability, high electrical insulation, and corrosion resistance.

[0039] Perfluorosulfonic acid (PFSA) has the characteristics of good heat resistance, chemical stability and high mechanical strength.

[0040] The instrument models involved in the following embodiments are as follows:

[0041] The test methods involved in the following embodiments are as follows:

[0042] Swelling rate in water: Cut the membrane into squares after drying, and record the diagonal length as D d Place it in deionized water and soak it at room temperature for 24 hours. Take it out after 24 hours and measure the diagonal length after soaking as D w , the swelling rate in water (ΔD) is calculated as follows:

[0043] ΔD=(D w -D d ) / D d ×100%

[0044] Tensile strength: The film was cut into samples with a length of 100 mm and a width of 15 mm. The tensile strength of the film was tested using an electronic universal testing machine with a tensile speed set at 10 mm / min.

[0045] Proton conductivity: The proton conductivity of the membrane was measured at 60°C using an electrochemical workstation.

[0046] Thermal decomposition temperature: The thermal stability of the film was tested using a thermogravimetric analyzer. The test environment was a nitrogen environment, the heating rate was set at 10°C / min, and the temperature test range was 30-800°C.

[0047] In the tests of swelling rate, tensile strength, proton conductivity and thermal decomposition temperature in water, the "membrane" is one of the spinning membranes prepared in Comparative Example 1, Comparative Example 2 and the composite electrospinning membranes prepared in Examples 1 to 3.

[0048] Examples 1 to 3

[0049] A composite electrostatic spinning membrane has a layered structure, which comprises an upper layer (perfluorosulfonic acid polymer layer), a middle layer (spinning membrane) and a lower layer (perfluorosulfonic acid polymer layer) from top to bottom. The upper layer, the middle layer and the lower layer have the same area. The upper layer comprises perfluorosulfonic acid, the middle layer comprises polyimide and perfluorosulfonic acid, the lower layer comprises perfluorosulfonic acid, the thickness of the composite electrostatic spinning membrane is D1 μm, the thickness of the middle layer is D2 μm, the thickness of the upper layer is D3 μm, the thickness of the lower layer is D4 μm, and the ratio of polyimide to perfluorosulfonic acid in the middle layer is X by mass.

[0050] The method for preparing the composite electrospinning membrane comprises the following steps:

[0051] Step 1, transferring the composite solution to a syringe of an electrospinning device for electrospinning, drying the composite solution in an oven at 60° C. for 12 hours after the electrospinning is completed to remove residual solvent, and hot pressing the composite solution at 100° C. and 0.8 MPa for 30 minutes to obtain a spinning membrane, wherein the composite solution comprises: polyimide and perfluorosulfonic acid, in the composite solution, the ratio of polyimide to perfluorosulfonic acid is Y by weight, the spinning rate of electrospinning is A mL / h, the voltage of electrospinning is B KV, and the distance between the spinneret and the receiving device is C cm;

[0052] The method for obtaining the composite solution is as follows: a polyimide solution and a perfluorosulfonic acid solution are mixed, and the mixture is stirred at 55° C. for 2.5 hours until the mixture is uniform, to obtain a composite solution, wherein the polyimide solution comprises polyimide, wherein the polyimide content in the polyimide solution is 13wt%, and the perfluorosulfonic acid solution is a mixture of perfluorosulfonic acid powder and a fourth solvent, wherein the content of perfluorosulfonic acid in the perfluorosulfonic acid solution is 5wt%.

[0053] Among them, the method for preparing a polyimide solution comprises: in a nitrogen atmosphere, in a three-necked flask, adding a second solution to a first solution in three times under stirring conditions (each time with an interval of 2 minutes to control the reaction rate), stirring at 20°C for 8 hours until uniform, sealing the bottle mouth with a sealing film to ensure airtightness, and obtaining a polyamic acid solution, wherein the first solution is a mixture of a diamine and a first solvent, the diamine is 3,3'-dimethyl-4,4'-diaminodiphenylmethane (DMMDA), the ratio of the mass fraction of the diamine to the volume fraction of the first solvent is 1:9, the unit of the mass fraction is g, and the unit of the volume fraction is mL; the second solution is a mixture of a dianhydride and a second solvent, the dianhydride is BPDA, the ratio of the mass fraction of the dianhydride to the volume fraction of the second solvent is 1:10, the unit of the mass fraction is g, and the unit of the volume fraction is mL. The polyamic acid solution and the third solvent are mixed and stirred until uniform to obtain a third solution, wherein the solid content of the third solution is 12wt%. The third solution and an imidizing agent are mixed, and stirred at room temperature for 24h to obtain a polyimide solution, wherein the imidizing agent is a mixture of acetic anhydride and pyridine, and the ratio of diamine, dianhydride, acetic anhydride and pyridine is 2.12:2.12:4:1 in terms of the amount of substance, and the third solvent is N-methylpyrrolidone (NMP).

[0054] The method for obtaining the first solution is: mix the diamine and the first solvent evenly to obtain the first solution, specifically: pour the first solvent into a three-necked flask, then add the diamine (DMMDA) powder into the three-necked flask, adjust the N2 gas flow to 0.2MPa, make N2 emit evenly, and stir at a speed of 150r / min until it is uniform; the method for obtaining the second solution is: mix the dianhydride and the second solvent evenly to obtain the second solution, the first solvent and the second solvent are each N-methylpyrrolidone (NMP).

[0055] The method for preparing a perfluorosulfonic acid solution comprises: mixing perfluorosulfonic acid powder and a fourth solvent, reacting in a reactor at 150° C. for 4 hours to obtain a perfluorosulfonic acid solution, wherein the fourth solvent is N-methylpyrrolidone.

[0056] Step 2: Use a cast coating method to coat the perfluorosulfonic acid solution on both sides of the spinning membrane, let it stand for 20 minutes to allow the perfluorosulfonic acid solution to fully penetrate, and dry it in a suspended vacuum drying oven at 80° C. for 8 hours to obtain a composite electrospinning membrane.

[0057] D1, D2, D3, D4, X, Y, A, B and C are shown in Table 1.

[0058] Table 1

[0059]

[0060] Comparative Example 1

[0061] A method for preparing a spinning membrane is the same as step 1 of Example 1.

[0062] The thickness of the spun membrane prepared in Comparative Example 1 is 20.4 um.

[0063] Comparative Example 2

[0064] A method for preparing a composite electrospinning membrane is basically the same as that of Example 2, except that step 1 of Comparative Example 2 is not subjected to hot pressing.

[0065] The thickness of the composite electrospinning membrane prepared in Comparative Example 2 is 38 um, and the thickness of the spinning membrane prepared in step 1 of Comparative Example 2 is 26 um.

[0066] Table 2

[0067]

[0068] As can be seen from Table 2, compared with Examples 1 to 3, when the content of polyimide (PI) increases, the swelling rate of the composite electrospinning membrane in water decreases, the thermal decomposition temperature and tensile strength increase, the limiting current density decreases, and the methanol permeation is less. When the content of perfluorosulfonic acid is high, the proton conductivity (proton conductivity) of the composite electrospinning membrane is high, indicating that perfluorosulfonic acid can improve the proton conductivity of the composite electrospinning membrane. Among them, proton conductivity is an important criterion for judging proton exchange membranes. Example 1 has the highest proton conductivity, other parameters have good performance, and the overall performance is the best. The composite electrospinning membrane of the present invention has a high thermal decomposition temperature and is not easy to decompose under high temperature conditions, which improves the problem that the conductivity of the perfluorosulfonic acid membrane decreases significantly under high temperature conditions; the composite electrospinning membrane of the present invention has a low swelling rate in water and good dimensional stability. Therefore, the present invention compounds polyimide (PI) with perfluorosulfonic acid, and on the premise of ensuring high proton conductivity, improves the thermal stability and mechanical stability of the composite electrospinning membrane and reduces the methanol permeability.

[0069] Analysis of the composite electrospinning membrane prepared in Example 1 and the spinning membrane prepared in Comparative Example 1 shows that the upper and lower layers of the composite electrospinning membrane contain perfluorosulfonic acid, which is beneficial to increase proton conduction and can reduce methanol permeation to a certain extent.

[0070] Analysis of the composite electrospinning membranes prepared in Example 2 and Comparative Example 2 shows that reducing the hot pressing treatment during the membrane preparation process will reduce the proton conductivity of the composite electrospinning membrane, increase the methanol permeation, and deteriorate the battery performance. This is because the hot pressing treatment increases the density of the spinning membrane on the one hand, and on the other hand, the hot pressing treatment improves the mechanical strength of the spinning membrane to a certain extent.

[0071] The present invention prepares a spinning membrane by electrostatic spinning, thereby improving the mechanical strength and anti-swelling property of the spinning membrane, and also has the advantage of reducing methanol permeability. Perfluorosulfonic acid polymer layers are coated on the upper and lower surfaces of the spinning membrane to obtain a composite electrostatic spinning membrane, which can increase the proton conductivity of the composite electrostatic spinning membrane to a certain extent.

[0072] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A composite electrospinning membrane, characterized in that: The composite electrostatic spinning membrane is a layered structure, which comprises an upper layer, a middle layer and a lower layer from top to bottom. The upper layer comprises perfluorosulfonic acid, the middle layer comprises polyimide and perfluorosulfonic acid, and the lower layer comprises perfluorosulfonic acid.

2. The composite electrospinning membrane according to claim 1, characterized in that: The thickness of the composite electrostatic spinning membrane is 25-40 μm.

3. The composite electrospinning membrane according to claim 1, characterized in that: The thickness of the middle layer is 15 to 25 μm, the thickness of the upper layer is 4 to 8 μm, and the thickness of the lower layer is 4 to 8 μm.

4. The composite electrospinning membrane according to claim 1, characterized in that: In terms of mass fractions, the ratio of the polyimide to the perfluorosulfonic acid in the intermediate layer is (0.1-1.5):(0.01-0.1).

5. The method for preparing a composite electrospinning membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1, electrospinning the composite solution, drying it, and hot pressing it to obtain a spinning membrane, wherein the composite solution comprises: polyimide and perfluorosulfonic acid, and in the composite solution, the ratio of polyimide to perfluorosulfonic acid is (0.1-1.5):(0.01-0.1) by weight; Step 2: coating the perfluorosulfonic acid solution on both sides of the spinning membrane, allowing it to stand and dry to obtain a composite electrospinning membrane.

6. The preparation method according to claim 5, characterized in that: In step 1, the method for obtaining the composite solution is: mixing the polyimide solution and the perfluorosulfonic acid solution until they are uniform to obtain the composite solution.

7. The preparation method according to claim 6, characterized in that: The polyimide solution comprises polyimide, and the content of polyimide in the polyimide solution is 8-14 wt %; the perfluorosulfonic acid solution comprises perfluorosulfonic acid, and the content of perfluorosulfonic acid in the perfluorosulfonic acid solution is 3-6 wt %.

8. The preparation method according to claim 5, characterized in that: In step 1, the hot pressing treatment is: hot pressing for 5 to 60 minutes at 60 to 120°C and 0.2 to 2MPa; in step 1, the spinning rate of the electrospinning is 0.8 to 2.0 mL / h, the voltage of the electrospinning is 10 to 30 KV, and the distance between the spinneret and the receiving device is 15 to 30 cm.

9. Use of one of the composite electrospun membrane according to claim 1 and the composite electrospun membrane obtained by the preparation method according to claims 5 to 8 in improving the thermal stability, mechanical stability and / or proton conductivity of a diaphragm.

10. Use of one of the composite electrospun membrane according to claim 1 and the composite electrospun membrane obtained by the preparation method according to claims 5 to 8 in suppressing the methanol permeability of a diaphragm.